2022
DOI: 10.3389/fpls.2022.1017840
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression of TIFY family in cassava (Manihot esculenta Crantz)

Abstract: Plant-specific TIFY [TIF(F/Y)XG] proteins serve important roles in the regulation of plant stress responses. This family encodes four subfamilies of proteins, JAZ (JASMONATE ZIM-domain), PPD (PEAPOD), ZML (Zinc-finger Inflorescence-like), and TIFY. In this work, a total of 16 JAZ, 3 PPD, 7 ZML, and 2 TIFY genes were found in cassava (Manihot esculenta Crantz) at the genome-wide level. The phylogenetics, exon-intron structure, motif organization, and conserved domains of these genes were analyzed to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…Almost all MeSRS genes were upregulated following PEG and NaCl treatments ( Figure 9 ), suggesting that they play a role in the regulation of diverse stress-related responses. Interestingly, the changes in gene expression and time across various treatments are not simple linear connections, indicating that the regulation of distinct MeSRS family members is a complex process, as corroborated by other studies [ 28 , 47 ]. Although our findings suggest that the MeSRS genes respond to phytohormone stimulation and abiotic stress, much more research is required to fully understand this response mechanism.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Almost all MeSRS genes were upregulated following PEG and NaCl treatments ( Figure 9 ), suggesting that they play a role in the regulation of diverse stress-related responses. Interestingly, the changes in gene expression and time across various treatments are not simple linear connections, indicating that the regulation of distinct MeSRS family members is a complex process, as corroborated by other studies [ 28 , 47 ]. Although our findings suggest that the MeSRS genes respond to phytohormone stimulation and abiotic stress, much more research is required to fully understand this response mechanism.…”
Section: Discussionsupporting
confidence: 73%
“…Fragments per kilobase of transcript per million reads mapped (FPKM) values were calculated to evaluate the gene expression. Log 2 -transformed heatmaps of all MeSRS genes were produced using TBtools software [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the hormone response elements, MeJA and ABA response elements are numerously, and a few other hormone response components. A number of plant hormones, including ABA, SA, and JA, have a role in stress reactions by triggering the transcription of genes involved in defense(Zheng, Wan, et al, 2022). Which shown that PnTLPs may be susceptible to MeJA and ABA regulation and thus play a role in plant growth and development as well as in adversity stress, which is generally consistent with the studies in watermelon(Ram, Danish, et al, 2022), woodland strawberry, and Hickory(Li, Xu, et al,…”
supporting
confidence: 86%
“…In this study, the number of proteins identified from the E. japonica genome, 26, was greater than the TIFY proteins in P. persica [ 2 ], A. thaliana [ 4 ], P. trichocarpa [ 12 ], O. sativa [ 10 ], and V. viniferas [ 7 ]; however, it was less than that in M. domestica [ 11 ], G. max [ 26 ], Manihot esculenta Crantz [ 43 ], and Brassica napus [ 45 ]. Gene duplication events are the main drivers of rapid gene family expansion and evolution.…”
Section: Discussionmentioning
confidence: 99%